Cardiohepatic interactions in heart failure: clinical and therapeutic implications. Issue 3 (9th October 2017) - Nikolaou, M.; Mebazaa, A.
Abstract: Liver involvement in chronic heart failure has long been recognized and reflects the systemic hemodynamic changes that occur during the evolution of heart failure syndrome. Apart from venous congestion and backward failure, other fundamental mechanisms also exist such as decreased hepatic blood flow, decreased arterial saturation, and sinusoidal thrombosis. In the acute setting, the decrease in cardiac output, accompanied by severe and profound hypotension is the main cause of acute liver injury, whereas increased venous pressure also plays an important role. The biochemical dominance of a cholestatic profile is rather related to congestion and increased systemic venous pressures, whereas the hepatotoxic profile is rather related to hypoperfusion. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5608949/Activity.aspx